Vocabulary Knowledge and Inferential Reading Comprehension of Senior High School Students: A Descriptive-Correlational Inquiry - Royeras, Julie T.; Sumayo, Gideon S. (East Asian Journal of Multidisciplinary Research, 2024)
This quantitative study employing descriptive-correlation research design is aimed to determine the vocabulary knowledge, the inferential reading comprehension, and whether there is a significant relationship between the vocabulary knowledge and inferential reading comprehension of the respondents. More so,it aimed to determine if there is a significant relationship between the vocabulary knowledge and inferential reading comprehension of senior high school students. The respondents to this study were two hundred sixty senior high school students at a public school in Libungan, Cotabato, Philippines. Two survey questionnaires were adopted to gather the needed data. The data gathered were tallied, computed, and interpreted using frequency counts, percentages, means, and Pearson R correlation.